Fat-specific transgenic expression of resistin in the spontaneously hypertensive rat impairs fatty acid re-esterification - Pravenec, M; Kazdová, L; Cahová, M; Landa, V; Zídek, V; Mlejnek, P; Simáková, M; Wang, J; Qi, N; Kurtz, T W (International journal of obesity (2005), 2006)
OBJECTIVE: To investigate the mechanism by which fat-specific transgenic expression of resistin affects fatty acid metabolism in the spontaneously hypertensive rat (SHR). DESIGN: Basal- and adrenaline-stimulated lipolysis, basal- and insulin-stimulated lipogenesis as well as the site (glycerol versus acyl moiety) of glucose incorporated into triglycerides were determined in adipose tissue isolated from SHR-Resistin transgenic and SHR control rats. RESULTS: A moderate expression of transgenic resistin in adipose tissue was associated with significant increase in the FFA/glycerol ratio during adrenaline-stimulated lipolysis in the SHR-Resistin transgenic rats (3.27+/-0.26) compared to SHR controls (2.11+/-0.10, P=0.0005). Transgenic SHR also exhibited a significant decrease in FFA re-esterification in adipose tissue (approximately by 23%). CONCLUSION: These findings raise the possibility that the prodiabetic effects of transgenic resistin may be partly mediated by increased FFA release from adipose tissue due to impaired FFA re-esterification in adipocytes.
Keywords: Glycerol; tuková tkáň; kyseliny mastné neesterifikované; glycerol; Epinephrine; geneticky modifikovaná zvířata; Resistin; krysa rodu Rattus; zvířata; lipolýza; glukosa; Esterification; resistin; Adipocytes; Animals, Genetically Modified; tukové buňky; adrenalin; potkani inbrední SHR; Glucose; Fatty Acids, Nonesterified; Rats; Animals; Lipolysis; Rats, Inbred SHR; Adipose Tissue; esterifikace